Genetic structure of Ethiopian finger millet landraces and genome-wide association mapping for agronomic and nutritional traits - Gebreyohannes, Adane; Shimelis, Hussein; Gimode, Davis M.; Grandham, Prasad; Valluri, Vinod Kumar; Nida, Habte; Moenga, Susan M.; Ojiewo, Chris Ochieng; Kilian, Benjamin; Odeny, Damaris Achieng (Springer, 2025)
Finger millet (Eleusine coracana subsp. coracana) (2n = 4x = 36) remains one of the most important millets in East Africa (EA), where it was most likely domesticated along the highlands of Ethiopia and Uganda. The goal of the current study was to understand the population structure of the Ethiopian finger millet landraces and identify quantitative trait nucleotides (QTNs) and haplotypes associated with agronomic and nutritional traits. In a field evaluation across three environments, 448 genotypes were assessed for days to flowering (DTF), days to maturity (DTM), thousand seed weight (TSW), grain yield (GY), stay-green score (STG), and drought score (DrtSc). The harvested grain was analyzed for Fe and Zn contents. A subset of 391 genotypes was skim-sequenced, generating 24,112 high-quality SNPs that were employed for population structure, association mapping, and haplotype analysis. Seventy marker-trait associations were detected including 15 major QTNs with more than 30% phenotypic variance explained (PVE) for all traits except STG and GY. Pleiotropic major QTNs were identified for DTM/DTF and Fe/Zn on chromosomes 9B and 2B, respectively. Haplotype analysis of major QTNs identified 54 significant haplotype blocks and 2 additional haplotypes for a multidrug ABC transporter gene family like protein on chromosome 4A that was associated with PTH. Favorable haplotypes from pleiotropic DTM/DTF and Fe/Zn QTNs were present in 13 and 12 genotypes respectively, majority from Tigray region. Two genotypes from Tigray and one from Amhara harbored favorable haplotypes for DTM/DTF and Fe/Zn. These findings provide invaluable insights for targeted breeding to enhance finger millet resilience, nutritional profile, and yield.